Distribuição espacial dos poliquetas (ANNELIDA, POLYCHAETA) dos Recifes de arenito na praia da Pedra Rachada (Paracaru - Ceará) - Sousa, Rossana Cristina de Azevedo (2006)
Sandstone rock reefs consist of consolidated substrata with a high fauna and flora diversity, where polychaetes represent a very important group. This study aims to contribute to the knowledge about polychaete annelids biodiversity on the coast of Ceará and their spatial distribution on hard substratum. The sampling took place on the reefs at Pedra Rachada beach (Paracuru-CE) and was carried out during low spring tides in August 2004 (dry season) and May 2005 (rainy season). A transect was placed perpendicularly to the coastline, throughout which samples, 10m apart from each other, were collected using a 25x25cm square. The sampled area was divided in three zones: lower, middle, and higher reefs. Considering the two studied seasons, 1315 specimens were identified and distributed in 60 polychaete species pertaining to 25 families and 42 genera. The most abundant families were Eunicidae, Orbinidae and Neredidae. Most of the found species are either carnivores, herbivores or burrowers. The typical species of the studied areas were Eunice cariboea, Naineris dendritica, Nematonereis hebes and Lysidice ninetta. No significant difference was observed in the absolute abundance of the species between the studied periods. However, a significant difference was observed between the lower and higher zones. During the dry season, the major abundance of individuals was found at the higher reef, whereas during the rainy season it was found at the lower reef. Nereis riisei was the only specie to present significant difference in its average abundance between the studied periods. The sandstone rock reef polychaetes at Pedra Rachada beach presented a distribution strongly related to the substratum features.